Performance Evaluation and Stability of Maize (Zea mays L.) Genotypes for Grain Yield Using AMMI and GGE Biplot - Berhanu Bilate Daemo; Getahun Bore Wolancho; Zeleke Ashango Arke; Dawit Dalga Wakalto; Mesele Haile Onu (International Journal of Agronomy)
It is a fact that the performance of most crop genotypes varies across environments due to genotype-environment interactions. Sharing knowledge about maize genotypes that are well-adapted and high-yielding in specific environments is essential for smallholder farmers to boost their productivity. A field trial was established in three locations during the 2019 and 2020 growing seasons to identify and select better-adapted high-yielding maize genotypes for production. A total of 10 improved varieties were evaluated using a randomized complete block design with three replications. The AMMI analysis of variance showed grain yield significantly (p≤0.001) influenced by genotype-environment interaction. This suggests that different genotypes showed varying grain yield performance across environments, implying the opportunity to choose effective genotypes suitable for both specific and broad adaptability. Moreover, the combined analysis of variance showed that genotype-environment interaction significantly influenced plant height, ear height, dry biomass yield, and hundred-kernel weight. The sum of squares factor explained that grain yield variation was contributed by the genotype (71.22%), followed by the environment (16.54%) and the genotype-environment interaction effect (12.24%) of the total variation. Genotypes BH-661, BH-549, and BH-546 demonstrated superior performance and stability, surpassing the national maize mean productivity and indicating broad adaptability. The AMMI analysis, GSI, and GGE biplot confirmed their robustness and high yield potential, especially for BH-661 and BH-549, making them optimal for variable conditions. Therefore, BH-661 and BH-549 are selected as stable genotypes for production in all agroecologies suitable for maize in the Dawuro zone.